Ophthalmology - Yanoff, Myron; Duker, Jay S. 1958-; 0000106671 (Mosby, 2000)
A reference covering various aspects of ophthalmology. This work combines genetics, diagnostic tips and techniques, proven management strategies, surgical approaches, drugs and more. An esteemed author team and contributions of hundreds of top-tier practitioners provide guidance on practically ophthalmic conditions and procedures